Catalytic fast pyrolysis of soybean hulls: focus on the products - Toro Trocho, José Luis; De Haro Del Río, David Alejandro; Sandoval-Rangel, Ladislao; Bustos-Martínez, Diana; García-Mateos, Francisco José; Ruiz-Rosas, Ramiro Rafael; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás; Carrillo-Pedraza, Eileen Susana (Elsevier, 2022)
Catalytic upgrading (with HZSM-5 zeolite) of the fast pyrolysis volatiles obtained from soybean hulls, a low cost and highly available biomass waste, has been investigated. The composition and yield of solid, liquid and noncondensable gas fractions obtained in the 400–600 ºC range during fast pyrolysis (FP) and catalytic fast pyrolysis (CFP) have been compared. The solid, liquid and non-condensable gas fraction obtained during FP and CFP have been characterized and compared. FP of soybean hull delivers liquid yields from 38% to 45% as temperature increases, while CFP slightly decreases the liquid yield to 37–42%. The characterization of the bio-oil has revealed that CFP increases more than 21% the amount of high-value species such as phenols, along with improvements of 30% in the heating value and reduction of the total acidity number by 15%. The biogas yield increase in CFP due to the deoxygenation and cracking reactions catalyzed by zeolite HZSM-5. The composition in FP shifts from being mostly CO2 and CO at 400 ºC towards a higher presence of hydrogen, methane and C2-C3 hydrocarbons at 500–600 ºC. CFP at 500 ◦C and 600 ◦C enhances the formation of hydrogen, methane and paraffinic C2-C3 hydrocarbons, which boosts the heating value of the gas to more than 15 kJmol 1. CFP does not cause any substantial changes in char composition, which is enriched in carbon while losing volatile matter as pyrolysis temperature increases and with char heating values between 25 and 27 MJ Kg 1. The presence of narrow microporosity has been confirmed by CO2 physisorption, while SEM images of the char reveal the presence of macropores. These results highlight the benefits of CFP for enhancing the production of bioenergy and bioproducts from soybean hulls.
https://openpolicyfinder.jisc.ac.uk/id/publication/12454
Keywords: Catálisis; Energía de la biomasa; Pirólisis; Fast pyrolysis; Biofuel; Char; Soybean hulls